Tamquam lupi rapaces: Dynamics of the Image of the Venetian Army in Dalmatian Hagiography - Marinković, Ana (Array, 2010)
The paper is analysing the changing image of the Venetian army and the episode of the Tragurian holy theft in 1171. The first part of the paper is focusing on the topos of lupi rapaces and its use around the year 1200, whereas the second part scrutinises the early modern variants of the narrative by Dalmatian and Venetian authors.